2000
DOI: 10.3354/meps203047
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in δ13C and δ15N of size-fractionated plankton at a coastal station in the northern Baltic proper

Abstract: Seasonal cycles of δ 13 C and δ 15 N in dissolved organic carbon and size-fractionated plankton, ranging from bacteria to the jellyfish Aurelia aurita, were studied during a 1 yr cycle at a coastal station in the Baltic Sea. The observed isotopic changes were found with time lags in all size-fractions of plankton. The δ 13 C showed a bimodal cycle with 2 local maxima, the first coinciding with the spring bloom and the second with the autumn bloom. In δ 15 N, the annual cycle was trimodal with 3 local maxima. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
169
3
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(201 citation statements)
references
References 30 publications
16
169
3
13
Order By: Relevance
“…In the literature, δ 13 C isotopic increases are reported to occur synchronously with spring phytoplankton blooms (Canuel et al, 1995, Rolff, 2000. Here, the high variability of primary production (Chl a, fig.1) and seston (δ 13 C and δ 15 N values) was not associated with similar variations of the two stable isotopes in the tissues.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In the literature, δ 13 C isotopic increases are reported to occur synchronously with spring phytoplankton blooms (Canuel et al, 1995, Rolff, 2000. Here, the high variability of primary production (Chl a, fig.1) and seston (δ 13 C and δ 15 N values) was not associated with similar variations of the two stable isotopes in the tissues.…”
Section: Discussionmentioning
confidence: 41%
“…Since the early work of Stephenson et al (1984), several authors have explored seasonal stable isotopic variation in marine organisms (Goering et al, 1990;Riera et al, 1996, Kang et al, 1999Rolff, 2000). Peterson and Fry (1987) and Peterson (1999) emphasized the limitations of isotopic measures, and the need to do both temporal and spatial sampling to fully understand the observed variations.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic seasonal cycle has been reported in several studies. Rolff (2000) reported a bimodal distribution of δ 13 C, with a spring and autumn maximum enrichment for size-fractionated plankton in the Baltic Sea. Xu et al (2005) found enrichment of δ 13 C in seston and lake anchovy with the progression of the summer bloom.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton as the marine end member for d 13 C DOC in the open Baltic Sea water column is known to use riverine DIC for production and, thus, areas more influenced by riverine DIC show lighter d 13 C values in phytoplankton. Rolff and Elmgren (2000) measured the d 13 C signature of phytoplankton in the Bothnian Bay between -25% and -27%, in the Bothnian Sea between -22% and -24%, and in the Baltic proper between -19% and -22% (Rolff and Elmgren 2000). The d 13 C signature of phytoplankton is also known to vary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mean difference between the measured and the calculated ratios was 13.5%. seasonally because of varying riverine DIC discharges (Chanton and Lewis 1999;Rolff 2000).…”
Section: Discussionmentioning
confidence: 99%